Interleukin-34 is present at the fetal-maternal interface and induces immunoregulatory macrophages of a decidual phenotype in vitro - Lindau, R; Mehta, R B; Lash, G E; Papapavlou, G; Boij, R; Berg, G; Jenmalm, M C; Ernerudh, J; Svensson-Arvelund, J (Human reproduction (Oxford), 2018)
Is the newly discovered cytokine interleukin (IL)-34 expressed at the human fetal-maternal interface in order to influence polarization of monocytes into macrophages of a decidual immunoregulatory phenotype? IL-34 was found to be present at the fetal-maternal interface, in both fetal placenta and maternal decidua, and it was able to polarize monocytes into macrophages of a decidual phenotype. IL-34 was shown to bind to the same receptor as macrophage-colony stimulating factor (M-CSF), which has an important immunomodulatory role at the fetal-maternal interface, for example by polarizing decidual macrophages to an M2-like regulatory phenotype. IL-34 is known to regulate macrophage subsets, such as microglia and Langerhans cells, but its presence at the fetal-maternal interface is unknown. The presence of IL-34 at the fetal-maternal interface was evaluated by immunohistochemistry (IHC) and ELISA in placental and decidual tissues as well as in isolated trophoblast cells and decidual stromal cells obtained from first trimester elective surgical terminations of pregnancy (n = 49). IL-34 expression was also assessed in third trimester placental biopsies from women with (n = 21) or without (n = 15) pre-eclampsia. The effect of IL-34 on macrophage polarization was evaluated in an in vitro model of blood monocytes obtained from healthy volunteers (n = 14). In this model, granulocyte macrophage-colony stimulating factor (GM-CSF) serves as a growth factor for M1-like polarization, and M-CSF as a growth factor for M2-like polarization. First trimester placental and decidual tissues were obtained from elective pregnancy terminations. Placental biopsies were obtained from women with pre-eclampsia and matched controls in the delivery ward. Polarization of macrophages in vitro was determined by flow-cytometric phenotyping and secretion of cytokines and chemokines in cell-free supernatants by multiplex bead assay. Our study shows that IL-34 is produced at the fetal-maternal interface by both placental cyto- and syncytiotrophoblasts and decidual stromal cells. We also show that IL-34, in vitro, is able to polarize blood monocytes into macrophages with a phenotype (CD14highCD163+CD209+) and cytokine secretion pattern similar to that of decidual macrophages. The IL-34-induced phenotype was similar, but not identical to the phenotype induced by M-CSF, and both IL-34- and M-CSF-induced macrophages were significantly different (P < 0.05-0.0001 depending on marker) from GM-CSF-polarized M1-like macrophages. Our findings suggest that IL-34 is involved in the establishment of the tolerant milieu found at the fetal-maternal interface by skewing polarization of macrophages into a regulatory phenotype. Although it is clear that IL-34 is present at the fetal-maternal interface and polarizes macrophages in vitro, its precise role in vivo remains to be established. The recently discovered cytokine IL-34 is present at the fetal-maternal interface and has immunomodulatory properties with regard to induction of decidual macrophages, which are important for a healthy pregnancy. Knowledge of growth factors related to macrophage polarization can potentially be translated to treatment of pregnancy complications involving dysregulation of this process. This study was funded by grants from the Medical Research Council (Grant K2013-61X-22310-01-04), the Research Council of South-East Sweden (FORSS), and the County Council of Östergötland, Sweden. No author has any conflicts of interest to declare.